Transformasi Digital Perencanaan Proyek Konstruksi: Perbandingan BIM dan Metode Konvensional pada Proyek Gedung NICU - Puah, Putri Sri; Purwantoro, Almuntofa; Uda, Subrata Aditama K. A (Jurnal Civil Engineering Study, 2025)
Project planning in construction requires a high level of accuracy in calculating work volumes, cost estimation, and scheduling. Even minor errors in these stages can lead to budget inefficiencies and schedule delays. This study compares the calculation of volumes, costs, and project duration using conventional methods and Building Information Modeling (BIM) in the construction project of the Neonatal Intensive Care Unit (NICU) building at RSUD Pulang Pisau, Central Kalimantan, Indonesia. The conventional approach relies on 2D drawings and manual calculations, while the BIM approach integrates 3D modeling using Autodesk Revit and cost estimation using Excel RAB V.1.1, based on AHSP (Analisis Harga Satuan Pekerjaan), the Indonesian Standard for Unit Price Analysis. The BIM model was developed based on As-Built Drawings. The results show differences in volume calculations for several work items, influenced by the level of model detail and the calculation method applied. BIM-based volume takeoff is derived from actual geometric shapes, including detailed building components. Cost estimation through BIM resulted in a lower total value, showing a 3.78% cost efficiency compared to existing project data. The BIM-based schedule maintained the same total duration of 20 weeks as shown in the S-curve, but was enhanced with more structured and visualized progress tracking. This study highlights the differences in results and the technical factors influencing volume accuracy, cost efficiency, and time visualization between the two project planning approaches.